(untitled) (Nexo Revista Científica, 2022)
The development and implementation of the latest technologies allow achieving competitive advantages in the global market and open up a wide range of prospects in various fields of activity. High risks and significant initial investments have predetermined the need to develop the most accurate methods for assessing the effectiveness of innovations. Traditional methods of investment assessment allow analyzing the economic component of these projects but do not consider specific risks that have a predominant impact on the successful result of financing. The study shows the need for an individual approach to assessing the effectiveness of each innovative project implementation, which should take into account its social significance in conjunction with maximizing economic benefits. Calculations that allow obtaining a single criterion for choosing the most optimal variant of the project implementation are presented. Recommendations on the organization of effective deployment of the 5G network in the Russian Federation are given in the study’s conclusion.